Essays on Informality: The roles of financial inclusion, financial development, and gender - Vargas Romero, María Paula (2025)
This doctoral thesis investigates the relationship between informality, gender, and financial development and inclusion through two complementary empirical studies. The first paper is based on international data, it explores the long-run and short-run dynamics between informality, financial development, and financial inclusion using a dynamic heterogeneous panel data model applied to 152 countries over the period 2004–2017. The results suggest that greater financial inclusion and development significantly reduce informality in the long run, particularly in developing countries, although the strength and significance of these effects vary across regions. The second paper focuses on Peru, where informality is persistent and tends to affect women more. Using data from the Peruvian National Household Survey (ENAHO) and classifying informal workers into type-S (structural) and type-N (non-structural) categories based on self-reported reasons, it estimates a binary response model to assess the probability of being a structurally informal worker. Additionally, Oaxaca-Blinder and Ñopo decomposition techniques are employed to separate the explained and unexplained components of the gender gap in structural informality. The results indicate that women are less likely than males to remain in the informal sector due to structural reasons (type-S informal workers), and that most of the gender gap can be explained by observable characteristics. Both papers provide robust evidence on the financial and structural drivers of informality, offering distinct policy recommendations: promoting financial inclusion and development to reduce informality, and implementing targeted interventions to address gender-specific and behavioral constraints.